Legal Review of Electronic Signatures in Signing Notarial Deeds Reviewed from Law Number 2 of 2014 Concerning Amendments to Law Number 30 of 2004 Concerning the Position of Notary - Utomo, Didik Setyo (Sultan Agung Notary Law Review, 2024)
The signature in a notarial deed in the past was a wet or conventional signature, but with the development of the current era, there are many electronic signature practices. Notarial deeds with wet signatures have been recognized as valid in the eyes of the law, while notarial deeds with electronic signatures have not yet been recognized as valid, so it is necessary to analyze their nature in order to find legal arguments so that electronic signatures can be used in parallel in electronic certificates in civil procedural law. The legal force of the electronic signature needs to be analyzed if there is a dispute between parties to the electronic agreement and also the position of the electronic signature can or cannot be equated with the legal purpose of a conventional signature. This study uses a normative legal method with a statutory regulatory approach and a conceptual approach. The conclusion is that the validity of the electronic signature in a notarial deed, as stipulated in the Electronic Information and Transactions Law, is still not recognized.